Effect of Different Herbage Allowances from Mid to Late Gestation on Nellore Cow Performance and Female Offspring Growth until Weaning - Sousa, Luciana Melo [UNESP]; de Souza, William Luiz [UNESP]; Oliveira, Karla Alves [UNESP]; Cidrini, Iorrano Andrade [UNESP]; Moriel, Philipe; Nogueira, Henrique César Rodrigues; Ferreira, Igor Machado [UNESP]; Ramirez-Zamudio, Germán Dario; Oliveira, Ivanna Moraes de; Prados, Laura Franco; Resende, Flávio Dutra de [UNESP]; Siqueira, Gustavo Rezende [UNESP] (MDPI, 2024)
This study evaluated different herbage allowances from mid to late pregnancy on pre- and postpartum physiological responses, milk production, and the performance of Nellore cows and the preweaning growth of their female offspring. Sixty multiparous Nellore cows were blocked by their body weight (BW; 425 ± 36 kg) and body condition score (BCS; 3.67 ± 0.23, scale 1–5) and randomly allocated to twelve pastures. Treatments consisted of two different herbage allowances (HA) during pregnancy: low HA (LHA; 2.80 kg DM/kg of BW) and high HA (HHA; 7.60 kg DM/kg of BW). Both treatment groups were fed 1 g/kg BW of a protein supplement. After calving, all cow–calf pairs were combined in a single group. The effects of maternal treatment × day of the study were detected for herbage mass and allowance, the stocking rate and forage crude protein, and for cow BW, BCS, and carcass measures (p < 0.01). Milk yield corrected to 4% fat, while the levels of fat total solids and cow plasma IGF-1 and urea were different (p ≤ 0.04) between treatments. HHA offspring was heavier (p ≤ 0.05) at 120 days and at weaning. A high herbage allowance can be implemented from mid-gestation until calving to increase cow prepartum performance, post-partum milk yield and composition, and positively modulate female offspring preweaning growth.
Keywords: female calves; fetal programming; forage allowance; milk yield; Nellore